Effect of thermal dispersion on transient natural convection in a wavy-walled porous cavity filled with a nanofluid: Tiwari and Das’ nanofluid model; International Journal of Heat and Mass Transfer; Vol. 92 - Sheremet M. A. Mikhail Aleksandrovich (2016, 2016)
Title screen